Applied Biomechanics in Sports Performance, Injury Prevention and Rehabilitation (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
I am pleased to present this Special Issue on applied biomechanics in sports performance, injury prevention, and rehabilitation. Advances in modern technological devices have allowed sports scientists to gather increasingly detailed information about the sports field and movement performance analysis. The availability of a wide range of kinetic and kinematic parameters has led to significant improvements in our ability to analyze various aspects of sports performance. Additionally, biomechanical studies have facilitated the development of efficient movement patterns, proper postural habits, and energy conservation through the economy of movement. Proper biomechanical analysis can help athletes detect potential problems before injuries occur, allowing them to make conscious changes in the way they move and reduce the risk of injury. The main objective of this work is to cover the latest advances in biomechanics applied to improve sports performance, prevent injury risk, or facilitate optimal rehabilitation in athletes.